War on AIDS : Free from Poverty, Free from AIDS - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, noted that we will be judged on three counts: first, whether the we are serious about Africa's development and inclusion; second, whether we understand globally the nature of human security and sustainable development; and, third, whether the international community can face up to the global challenge of acquired immune deficiency syndrome (AIDS). More than 13 million Africans have already died of AIDS, 23 million are now living with human immunodeficiency virus (HIV) and AIDS, and 10 million African children have been orphaned by AIDS. The 21 countries with the highest rates of HIV are all in Africa. The Bank will provide governments with the maximum available funding to create and implement programs.